Buckling design of large steel silos with various slendernesses - Cao, Qing-shuai; Zhao, Yang (Journal of Zhejiang University. A. Science, 2017)
Large steel silos are typical kinds of thin-walled structure which are widely used for storing huge quantities of granular solids in industry and agriculture. In the present analyses, the buckling design of large steel silos subject to Eurocode-specified solid pressure is demonstrated. The finite element model is established using the commercial general purpose computer package ANSYS. Six types of buckling analyses are carried out for the geometrically perfect and imperfect models with and without consideration of material plasticity. The load cases of concentric discharge, discharge patch load, large eccentricity discharge, and large eccentricity filling are considered. The buckling behavior of six example steel silos with capacities of 30 000–60 000 m 3 is investigated. The silos’ slenderness ranges from 4.77 to 0.35, comprising very slender, slender, intermediate slender, squat, and retaining silos. The index called the ratio of capacity to steel consumption (RCS) is initially defined in the paper, which provides an effective measure for the economical design of steel silos. It is validated that the RCS index increases rapidly with the decrease of silo slenderness, and the storage efficiency of steel silo improved greatly as the slenderness changes from slender silo to retaining silo. The effects of patch load reveal that the buckling modes in the case of discharge patch load are very different from those of silos under concentric solid pressure, and the effect is unfavorable for buckling resistance of all levels of slenderness of the example silos, but contributes a small decrease to the RCS index (less than 10%). The buckling deformations from both the linear and nonlinear buckling analyses in large eccentric discharge are strongly asymmetrical arising from the circumferential and meridional non-uniform distribution of the solid pressures. The buckling is mainly governed by the non-uniform distribution of the solid pressure other than other influential factors such as the weld imperfection, geometrical and material nonlinearity, compared with the load case of concentric discharge. The RCS index of example silos under large eccentric discharge is reduced substantially, and is approximately half that of silos under concentric discharge. The linear and nonlinear buckling deformations in large eccentric filling are also asymmetrical, deviating from the center to the side where the most friction locates to the highest wall contact. The RCS index of example silos under large eccentric filling is also reduced substantially, and is approximately 70% that of silos under concentric discharge. This reveals that the large eccentricity both in discharging and filling could result in a strong decrease of storage efficiency of steel silos.